Optical Coherence Tomography Features Of Active And Inactive Retinal Neovascularization In Proliferative Diabetic Retinopathy. Issue 6 (June 2016) - Vaz-Pereira, Sara; Zarranz-Ventura, Javier; Sim, Dawn A.; Keane, Pearse A.; Smith, Rebecca; Egan, Catherine A.; Tufail, Adnan
Abstract : Purpose: To describe spectral domain-optical coherence tomography features of retinal neovascularization in proliferative diabetic retinopathy and thus to identify novel signs of new vessel activity. Methods: Retrospective, cross-sectional study. Data were collected over a 9-month period. Spectral domain optical coherence tomography scans were performed over areas of new vessel complexes (NVC) in both the disk and elsewhere, and were qualitatively graded by two masked observers. New vessel complexes activity was determined using clinical and angiographic criteria and correlated with spectral domain optical coherence tomography features. Results: Forty-three eyes of 30 patients with proliferative diabetic retinopathy were included. Sixty-one NVC lesions (neovascularization of the disk—37.7%, neovascularization elsewhere—62.3%) were captured by spectral domain-optical coherence tomography and analyzed. Among them, 63.9% were classified as active and 36.1% as quiescent. Five distinctive features were identified as significantly different between active and quiescent NVC: the presence of vitreous hyperreflective dots in active NVC ( P = 0.002) and the presence of epiretinal membrane ( P = 0.04), inner retinal tissue contracture ( P = 0.03), vitreous invasion ( P = 0.02), and protrusion towards vitreous ( P = 0.002) in quiescent NVC. Conclusion: In this exploratory study, the presence of vitreous hyperreflective dots, epiretinal membrane, inner retinal tissue contracture, vitreous invasion, and vitreous protrusion were identified as distinct signs of disease activity. Such parameters may be useful as a noninvasive imaging modality in eyes undergoing treatment for proliferative diabetic retinopathy.